1998
DOI: 10.2337/diacare.21.9.1445
|View full text |Cite
|
Sign up to set email alerts
|

Two-Step Islet Autoantibody Screening for Risk Assessment of Type 1 Diabetes in Relatives

Abstract: A two-step antibody screening, based first on GADA and IA-2A and then on ICA and IAA measurements in identified individuals, is likely to be a practical, sensitive, and effective strategy for predicting type 1 diabetes in first-degree relatives.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0
1

Year Published

1999
1999
2006
2006

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(17 citation statements)
references
References 0 publications
1
15
0
1
Order By: Relevance
“…[27,29,42,89,[92][93][94][95][96][97]102,104,105,107,[112][113][114] children [89,146]. The broadening of the autoimmune response to epitopes of different islet-cell antigens, commonly referred to as intermolecular epitope spreading, is associated with an increased probability of developing diabetes, which is also reflected by an enhanced T-cell reactivity to different islet-cell antigens [40,41,[146][147][148][149].…”
Section: Insulinmentioning
confidence: 99%
“…[27,29,42,89,[92][93][94][95][96][97]102,104,105,107,[112][113][114] children [89,146]. The broadening of the autoimmune response to epitopes of different islet-cell antigens, commonly referred to as intermolecular epitope spreading, is associated with an increased probability of developing diabetes, which is also reflected by an enhanced T-cell reactivity to different islet-cell antigens [40,41,[146][147][148][149].…”
Section: Insulinmentioning
confidence: 99%
“…GADAs and IA-2As were measured by radiobinding assay, using in vitro transcribed and translated recombinant human protein, as previously described (21). The thresholds for positivity were 3 U (GADA) and 1 U (IA-2A).…”
Section: Autoantibody Measurementsmentioning
confidence: 99%
“…There are several reports that describe the predictive characteristics of various autoantibodies (1)(2)(3)(4)(5)(6). We have previously shown that islet cell antibodies (ICA), antibodies to IA-2 (IA-2A), antibodies to GAD (GADA), and insulin autoantibodies (IAA) are all useful predictive markers of type 1 diabetes in siblings initially tested at or close to the time of diagnosis of the first affected child in the family (7).…”
mentioning
confidence: 99%